Cytolethal Distending Toxin Sequence and Activity in the Enterohepatic Pathogen Helicobacter hepaticus - Young, Vincent B. (American Society for Microbiology, 2000)
Little is known about the molecular pathogenesis of hepatitis and enterocolitis caused by enterohepatic Helicobacter species. Sonicates of the murine pathogen Helicobacter hepaticus were found to cause progressive cell distension, accumulation of filamentous actin, and G(2)/M cell cycle arrest in HeLa cell monolayers. The genes encoding this cytotoxic activity were cloned from H. hepaticus. Three open reading frames with closest homology to cdtA, cdtB, and cdtC from Campylobacter jejuni were identified. Sonicates of a laboratory strain of Escherichia coli carrying the cloned cdtABC gene cluster from H. hepaticus reproduced the cytotoxic activities seen with sonicates of H. hepaticus. Cytolethal distending toxin activity is a potential virulence determinant of H. hepaticus that may play a role in the pathogenesis of Helicobacter-associated hepatitis and enterocolitis.